Securing and authenticating healthcare records through blockchain technology. Issue 4 (3rd July 2020) - Pandey, Prateek; Litoriya, Ratnesh
Abstract: Healthcare data is important in making critical policy decisions, patients care, and medical diagnostics to name a few. Due to the importance and market demand, healthcare data is also vulnerable to cyber attacks. The centralized record keeping systems expose a single node for the attackers to attack. A decentralized system is computationally expensive but has the ability to be revolutionary by keeping the patient at the core and providing security, transparency, privacy, and interoperability of the electronic healthcare data. A blockchain is such an implementation of a distributed and decentralized system using reliable cryptographic algorithms. This paper proposes a secure blockchain based architecture tailored specifically to cater to the needs of e-healthcare systems.